A Professionalizing Process: An Intervention in Higher Education - Camacho-Javier, Minerva; López-del Castillo, José César (Revista Electrónica Educare, 2022)
Introduction. The lack of educational convergence in higher education is palpable in Mexico, with uneven progress in training by competencies, especially in the country’s south. The teaching staff is considered to be the main axis in the development of educational quality. Therefore, this research aims to know how a professionalizing process applied to a group of male and female teachers from a public higher education institution located in the south of the country is assumed, seeking the development of teaching competencies. Methodology. A collaborative and participatory longitudinal exploratory-descriptive action research was conducted. A professionalizing process was designed and applied in one of the most populated academic divisions of the educational institution (IE) that was the subject and object of the study. The research was conducted in one and a half years with a group of teachers selected for convenience and with interchangeable roles. Results. Through qualitative and quantitative indicators, the involvement of the teaching staff in the professionalizing process is shown. These indicators are voluntary participation, recognitions, dissemination of academic performance, evidence of teaching-learning by competencies, didactic-pedagogical interaction, and theory in practice. Discussion. The importance of an educational management with proactive leadership that practices a more cohesive curriculum towards interdisciplinary and transdisciplinary work is highlighted, seeking socially responsible management. Finally, collaborative and participatory action research guides towards a knowledge bridge for the development of teaching competencies; however, the continuity of this process is required to innovate in higher education.